Access of third-country nationals to jobs in the public administration and prospects in Italy and Germany in the light of euro-unification developments: Peer-reviewed article (Italian Review of Legal History, 2023)
The access of third-country nationals to public administrations was introduced by Law no. 97 of 6 August 2013, in order to put an end to two pre-litigation procedures initiated by the Commission, which extended the possibility of access to jobs in public administrations, in cases where European citizens were already entitled, to their non-EU family members with the right of residence, as well as to foreign citizens with a long-term EC residence permit (so-called “long-stayers”) or holders of refugee or subsidiary protection status. This study analyses the Italian legislation in this field, both in its original version and in subsequent amendments, and then refers to the situation in other EU Member States. The study is based on the conviction that the increased employment of foreigners, not only in the private sector (including the higher professional segments), but also in the various areas of the public service (as is the case to some extent in Germany), will enable Italy to better manage a diverse society, given the different cultural backgrounds of its inhabitants.
Keywords: Public Administration; non-EU immigrants; long-term residence permit; Directive; germany